Isolation of Gram-negative bacilli and Staphylococci, after two handwashing techniques, in Nursing students who perform hospital practices - Orellana Guevara, Raquel (2020)
Objective: The purpose of the research was the isolation of microorganisms of the genus Staphylococcus and Bacillus Gram negative after two handwashing techniques, during the laboratory practices of nursing students. Methodology: The research was correlational and transversal, carried out in May 2018; The participants were 40 students distributed in two groups (Control and experimental groups). Samples were taken by swab from recently washed hands. The 11-step clinical handwashing (CML) was applied in the control group and the 3-cycle CML in the experimental group, after training. Isolation, identification and microbial count was carried out in suitable and selective culture media. The data was processed in the Excel program, using tests of statistical significance and descriptive statistics. Results: Negative Staphylococcus cuagulase was isolated in 40% of the total participants; Depending on the type of washing this microorganism was found in 50% of participants who applied the 11-step CML, and in 30% of participants after the 3-stroke CML. Regarding the search for Gram-negative bacilli, Klebsiella spp was found in 5% of the total participants in the 3-stroke CML. Bacterial counts were lower in the 3-stroke CML and a statistically significant difference of p = 0.033 (p≤0.05) was obtained when comparing both washing techniques. Conclusions: There was a difference between the two handwashing techniques in bacterial counts, with greater growth after the 11-step CML, and lower growth in the 3-stroke CML. The most frequent microorganism was Staphylococcus cuagulase negative and in a minimum of samples, Klebsiella spp.